2020
DOI: 10.1152/ajprenal.00442.2019
|View full text |Cite
|
Sign up to set email alerts
|

Acyloxyacyl hydrolase regulates voiding activity

Abstract: Corticotropin-releasing factor (CRF) regulates diverse physiological functions, including bladder control. We recently reported that Crf expression is under genetic control of Aoah, the locus encoding acyloxyacyl hydrolase (AOAH), suggesting that AOAH may also modulate voiding. Here, we examined the role of AOAH in bladder function. AOAH-deficient mice exhibited enlarged bladders relative to wild-type mice and had decreased voiding frequency and increased void volumes. AOAH-deficient mice had increased nonvoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…Our previous studies show that AOAH-deficient mice mimic symptoms and comorbidities of IC/BPS [7, 13, 14]. Here we show that the pelvic pain phenotype and anxiety/depressive-like behavior can be regulated by microbiota (Figs 7 and 8).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Our previous studies show that AOAH-deficient mice mimic symptoms and comorbidities of IC/BPS [7, 13, 14]. Here we show that the pelvic pain phenotype and anxiety/depressive-like behavior can be regulated by microbiota (Figs 7 and 8).…”
Section: Discussionsupporting
confidence: 69%
“…2), suggesting that AOAH effects on gut gene expression lie elsewhere. Indeed, we previously reported that AOAH is a genetic regulator of the locus encoding corticotropin-releasing factor (CRF), in brain sites mediating bladder and stress responses where AOAH deficiency leads to increased Crf expression and stress responses [13, 14]. CRF alters gut function at multiple levels (reviewed in [50, 51]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations